ANALYSIS OF THE BASIC DIRECTIONS OF FIRE HOSES RUPTURE PRESSURES INCREASING - Myrkhalykov, Zh.U.; Stepanov, S.G.; Kaldybaev, R.T.; Aripbaeva, A.E.; Satayev, M.I. (Scientific Journal of Pedagogy and Economics, 2020)
The analysis of the main ways to increase the rupture pressure of these technical products was made based on the rupture pressures dependence in fire pressure hoses from the parameters of their woven reinforcing frame previously obtained by the authors. From a scientific and practical point of view, the main directions for increasing the bursting internal pressures in the FPH (Fire pressure hoses) are identified and analyzed. The developed methodology for calculating and designing of FPH is based on a relationship connecting internal hydraulic pressure p-burst with a breaking load N-burst in the weft thread and a number of other parameters. To assess the influence of the parameters of the FPH woven reinforcing framework on the value of the internal bursting pressure, the latex FPH with a diameter of 77 mm manufactured by BEREG (Russia) made of polyester yarns and designed for a working pressure of 1.6 MPa, was chosen as the object of study. The dependences of the bursting pressures values on the bursting strength of weft threads of FPH woven reinforcing frameworks, designed for a working pressure of 1.6 MPa, for various diameters of the arms cross sections are obtained. The influence of geometric densities on the basis and weft of the woven reinforcing frame on the value of internal burst pressure in the FPH is investigated. When calculating the FPH strength under the action of internal hydraulic pressure, the effect on the value of the burst pressure in latex FPH manufactured by BEREG (Russia), designed for a working pressure of 1.6 MPa, such parameters as sleeve radius, geometric densities of base and weft was studied. When designing and creating new types of FPH, it is necessary to take into account the influence of these parameters on the burst pressure value.